APPLICATION OF BENZYLADENINE (BA) IN THE FORM OF LANOLIN PASTE ON FLOWER-STALK BUDS SUCCESSFULLY INDUCED RE-BLOOMING OF HYBRID Phalaenopsis - Mukhaila Iryani; Yusnita Yusnita; Dwi Hapsoro; Kukuh Setiawan; Agus Karyanto (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2020)
Hybrid moth orchid (genus Phalaenopsis) is one of the most popular ornamentals in Indonesia. It has beautiful and long-lasting flowers, but cultivating this orchid is still become a challenging issues due to the need of specific condition to grow and long time period to re-blooming. Plant growth regulators (PGR) (i.e. Benzyladenine (BA)) has been widely documented as a flower-inducing substance in several orchids. However, the optimal concentration and its mechanism in inducing flower-stalk bud and re-blooming is still unclear. This research aimed to study the effects of BA application in the form of lanolin paste on hybrid Phalaenopsis flower-stalk buds. We conducted this study using completely randomized design with four replications at the greenhouse laboratory Faculty of Agriculture University of Lampung on August to December 2018. We divided the orchid into 5 group of BA concentration (0, 1000, 1500, 3000, or 6000 ppm). The sheath of the fourth or fifth buds of the flowers were carefully opened, then it smeared with BA. The percentage of bud break into flower spike or keiki, length of shoots or spike and number of open flowers were recorded until 10 weeks of observation. The results showed that, neither of the buds under the control treatment (without BA), 1000 ppm nor 1500 ppm BA broke and grew into keiki or spike. On the other hand, application of BA at 3000 ppm or 6000 ppm successfully induced 100% flower spikes on the buds treated. No keiki was formed in all buds treated. In addition, treatment of the buds with 6000 ppm BA produced longer flower spikes as well as more open flowers. We conclude that the application of BA (minimal 3000 ppm) successfully induced flower spike of hybrid Phalaenopsis.